Resveratrol ameliorates hepatic injury and modulates hepatic biomarkers of regeneration, apoptosis and survival in a rat model of blunt hepatic trauma - Yilmaz, N.; Yilmaz, A. F.; Ilhan, Y. S. (Comenius Univ, 2020)
OBJECTIVE: To investigate the protective potential of resveratrol (RES) in blunt hepatic trauma (BHT) by exploring the anti-inflammatory and histopathologic effects as well as modulatory effects on hepatic biomarkers of acute injury, regeneration, apoptosis and survival in a rat model of BHT. METHODS: A total of 21 Wistar Albino rats (weighing 120-250 g) were separated into 3 groups (n = 7 for each group), namely control group (CON; standard feeding), BHT group (BHT; blunt hepatic trauma plus observation) and trauma plus BES group (BHT-RES; blunt hepatic trauma plus intraperitoneal injection of 10 mg/kg RES). Serum levels for aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH) and bilirubin were measured on Day 7 and rats were sacrificed for histopathological (inflammation scores) and immunohistochemical [expression of proliferation marker (Ki-67) and apoptosis-related markers (Bcl-2, and Bax)] analyses in resected liver tissue. RESULTS: The highest levels for serum AST (p = 0.002), ALT (p = 0.002) and LDH (p = 0.002) were obtained from BHT group of rats, as followed by BHT-RES and control groups, respectively. The highest scores for Ki 67 (p = 0.002 for each), Bcl 2 (p = 0.002 for each) and Bax (p = 0.002 for each) were obtained from BHT-RES group of rats, as followed by BHT and control groups, respectively. Inflammation scores were significantly higher in BHT vs BHT-RES group (2.42 +/- 0.53 vs 1.42 +/- 0.53; p = 0.001) and both groups had higher inflammation scores than the control group (0.0 +/- 0.0; p = 0.001). CONCLUSION: In conclusion, our findings revealed for the first time that RES exerts promising hepatoameliorative effects against blunt hepatic injury as evidenced by decreased inflammation scores, parallel with improved hepatic histology, decreased serum transaminase activity as well as enhanced modulatory effect on regenerative and apoptotic processes in RES-treated rats subjected to experimentally-induced blunt hepatic trauma (Tab. 1, Fig. 1, Ref. 37). Text in PDF www.elis.sk
Keywords: blunt hepatic trauma; resveratrol; anti-inflammatory; histopathologic; transaminases; apoptosis; rats